On the structure of characteristic surfaces related with partial differential equations of first and higher orders. Pt 2 - Prykarpatska, N.K. (Нелінійні коливання, 2005)
The generalized characteristics method is developed in the framework of the geometric Monge picture. The Hopf – Lax-type extremality solutions to a wide class of Cauchy problem for nonlinear partial differential equations of first and higher orders are derived. The special Hamilton – Jacobi-type case is analized separately. The exact extremality Hopf – Lax-type solution for Cauchy problem to the nonlinear Burgers equation is received, its linearization to the Hopf – Cole expression and to the related Airy-type linear partial differential equation is found and discussed.